UZBEK AND FRENCH SPEECH ETIQUETTE UNITS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article reveals the important aspects of the speech etiquette units of the French and Uzbek peoples and the specific features of the use of these speech etiquette units in different life situations.